Fortification of Carica papaya fruit seeds to school meal snacks may aid Africa mass deworming programs: a preliminary survey - M. Kugo; L. Keter; A. Maiyo; J. Kinyua; P. Ndemwa; G. Maina; P. Otieno; E. M. Songok (BMC, 2018)
Abstract Background Soil transmitted helminths (STHs) are among the world's neglected tropical diseases. Morbidity due to STHs is greatest in school-age children who typically have the highest burden of infection. In 2001, WHO passed a resolution for the use of large-scale mass drug administration (MDA) to deworm vulnerable children through school based programs. Though effective, there is concern that MDA might not be sustainable over extended periods. Additionally the current MDA strategy does not consider child malnutrition, a very common malady in resource limited countries. We report a pilot evaluation of an innovation that bundles school feeding and deworming. Methods We designed a maize (corn) flour fortified with grounded dried papaya (Carica papaya) seeds and used it to prepare porridge as per the usual school meal recipe Children from three primary schools from Nandi County in Kenya were randomized into three arms: One school received 300 ml papaya fortified porridge daily (papaya group), the second school received similar serving of plain porridge without the pawpaw ingredient (control group) and the third school received plain porridge and the conventional MDA approach of one time 400 mg dosage of albendazole (albendazole arm). Prior to the randomization, an initial baseline stool microscopy analysis was done to determine presence and intensity of intestinal worms. Core indicators of nutrition-height, weight and hemoglobin counts were also assessed. The children were monitored daily for two months and final stool sample analysis and clinical monitoring done at the end of the study. Baseline and follow-up data were analyzed and compared through SAS version 9.1 statistical package. Results A total of 326 children participated in the trial. The overall prevalence of Ascaris lumbricoides was 29.4% (96), Trichuris Trichura 5.2% (17) and hookworm 1 (0.3%). Papaya seed fortified porridge reduced the Ascaris lumbricoides egg count by 63.9% after the two month period (mean 209.7epg to 75.7 p < 0.002) as compared to the albendazole arm 78.8% (129.5 epg to 27.5, p value 0.006). The control group showed an increase in egg count (42.epg to 56.3) though it was not statistically significant. Hemoglobin counts in the papaya group increased from a mean of 2 g/dL (11.5 g/dL to 13.5 g/dL, p < 0.001), as compared to the albendazole arm that increased by 1 g/dL (12.8-13.9, p < 0.001). No significant change was observed in the placebo arm (13.2 to 13.1). Interestingly the papaya group showed a significant reduction of children with Tinea capitis (ringworms) (54.4 to 34%, p < 0.002) as compared to the albendazole arm that showed an increase in ringworm infestation though not statistically significant (39.7 to 64.7% p = 0.608). Conclusion Papaya seed fortified porridge had a significant effect on reduction of Ascaris lumbricoides burden. It had a better nutritional outcome and effect on child fungal infections than albendazole. Its application as a routine school meal may aid current national school based nutrition and deworming programs in Africa. Trial registration This study was retrospectively registered at Clinicaltrials.gov Ref. NCT02725255 on 31st March 2016.